Análise da viabilidade técnica da operação de sistemas com geração distribuída no modo ilhado intencional - Deifelt, Samuel Vanderlei (2016)
The increasing demand for energy, coupled with the difficulties inherent in the implementation of large generation projects, significantly increased the use of energy resources from renewable energy sources, in order to better meet the energy market. Recent research shows that there are several benefits of using the Distributed Generation in relation to large enterprises Centralized Generation. In this sense, this work shows the results of studies conducted in order to verify the feasibility of taking advantage of the Distributed Generation to meet the remaining local loads in any power shortages Distributor. This operation is called Intentional Islanded Operation. In order to implement the intentional islanding operation of Distributed Generation, it is necessary to carry out specific studies to meet the levels of quality and continuity established by regulations and to ensure the safety of the electrical system. Thus, this work presents an analysis of the technical feasibility of intentional islanded operation of distributed generators, given the restrictions imposed resulting from Power Flow studies, Transient Stability and Short Circuit.